Oral and inhaled corticosteroids: Differences in P-glycoprotein (ABCB1) mediated efflux - Crowe, Andrew; Tan, A. (Elsevier, 2012)
There is concern that P-glycoprotein mediated efflux contributes to steroid resistance. Therefore, this study examined bidirectional corticosteroid transport and induction capabilities for P-glycoprotein (P-gp) to understand which of the systemic and inhaled corticosteroids interacted with P-gp to the greatest extent. Hydrocortisone, prednisolone, prednisone, methylprednisolone, and dexamethasone represented systemically active drugs, while fluticasone propionate, beclomethasone dipropionate, ciclesonide and budesonide represented inhaled corticosteroids. Aldosterone and fludrocortisone represented mineralocorticoids. All drugs were detected using individually optimised HPLC protocols. Transport studies were conducted through Caco-2 monolayers. Hydrocortisone and aldosterone had efflux ratios below 1.5, while prednisone showed a P-gp mediated efflux ratio of only 1.8 compared to its active drug, prednisolone, with an efflux ratio of 4.5. Dexamethasone and beclomethasone had efflux ratios of 2.1 and 3.3 respectively, while this increased to 5.1 for methylprednisolone. Fluticasone showed an efflux ratio of 2.3. Protein expression studies suggested that all of the inhaled corticosteroids were able to induce P-gp expression, from 1.6 to 2 times control levels. Most of the systemic corticosteroids had higher passive permeability (>20×10−6 cm/s) compared to the inhaled corticosteroids (>5×10−6 cm/s), except for budesonide, with permeability similar to the systemic corticosteroids. Inhaled corticosteroids are not transported by P-gp to the same extent as systemic corticosteroids. However, they are able to induce P-gp production. Thus, inhaled corticosteroids may have greater interactions with other P-gp substrates, but P-gp itself is less likely to influence resistance to the drugs.